Application of PDCA cycle in improving the awareness of postoperative health education among elderly patients with interventional therapy (PDCA循环在提高老年介入治疗患者术后健康宣教知晓率中的作用) - GUO Huihui (郭慧慧); XING Ying (邢英); JIN Yue (金悦); FANG Rui (方蕊) (中西医结合护理, 2022)
Objective To observe the effect of PDCA cycle in improving the awareness rate of health education among elderly interventional patients. Methods From January to April of 2021, 70 elderly patients undergoing interventional therapy were recruited as the research objects (post-activity group). The PDCA cycle method was adopted in the postoperative health education for elderly patients with interventional therapy. Another 70 patient receiving routine health education after interventional therapy were included as the pre-activity group. The patient awareness of health education, treatment compliance, mental status, sleep quality and quality of life were measure and compared between Pre-activity group and Post-activity group. Results The awareness rate of patient health knowledge in the post-activity group was significantly higher than that in the pre-activity group (97. 14% vs. 64. 29%, P<0. 05). The accuracy of oral medication time, regular follow-up monitoring rate, rate of identifying mistakes after PCI and correct lifestyle rate in the post-activity group were significantly higher than those in the pre-activity group(P<0. 01). The scores of Patient Health Questionnaire-9(PHQ-9) and Pittsburgh Sleep Quality Index(PSQI) in the post-activity group were significantly lower than those in the pre-activity group(P<0. 01). The score of Quality of life SF-36 questionnaire (SF-36) in the post-activity group wasgnificantly higher than those in the pre-activity group(P<0. 01). Conclusion The application of PDCA cycle in postoperative health education can increase the patient awareness and compliance with health knowledge, improve lifestyles, relieve the anxiety and depression, improve overall sleep quality and quality of life, and provide rehabilitation for elderly patients undergoing interventional therapy. (目的 探讨运用PDCA循环提高老年介入治疗患者健康宣教知晓率中的效果。方法 选取2020年9月—12月中国航天科工集团七三一医院收治的行介入治疗的老年患者70例设为活动前组, 采用常规健康教育。2021年1月将PDCA循环应用于健康教育管理, 并选取2021年1月—4月收治的行介入治疗的老年患者70例设为活动后组。观察2组健康教育知晓率、治疗依从性、心理状态、睡眠质量以及生活质量。结果 活动后组的健康知识知晓率97. 14%(68/70), 高于活动前组的64. 29%(45/70), 差异有统计学意义(P＜0. 05); 活动后组的口服药服药时间准确率、定期随访监测率、介入治疗术后误区认知率、正确生活方式率均高于活动前组, 差异有统计学意义(P＜0. 01); 活动后组的抑郁自评量表(PHQ-9)和匹兹堡睡眠质量指数(PSQI)评分均低于活动前组, 差异有统计学意义(P＜0. 01); 活动后组生活质量高于活动前组, 差异有统计学意义(P＜0. 01)。结论 PDCA循环应用于老年介入治疗患者术后健康宣教中, 可提高患者的健康知识知晓率和依从性, 改善患者负性情绪, 提高整体睡眠质量和生活质量, 对患者康复有重要意义, 值得推荐。)